CYBERCRIME-RITUALISM AND VICTIMIZATION IN CENTRAL SENATORIAL DISTRICT OF KWARA STATE, NIGERIA - Buhari Edun, Jimoh (African Journal of Social and Behavioural Sciences, 2024)
The general aim of the study is to assess cybercrime, ritualism, and criminal victimisation in the Kwara Central Senatorial District of Kwara State, Nigeria. Two specific objectives are considered, which include the prevalence of cybercrime-ritualism and the effect of invocation on criminal victimization. The development of information and communication technology (ICT) has revealed an ever-expanding knowledge field that seeks to bring global activities to everyone doorstep. Apart from facilitating the emergence of a global village, the increased access to the internet has opened a window for both legitimate and illegitimate transactions. A thematic review of the literature is carried out. The study used Rational Choice Theory for its theoretical framework. The study adopted a cross-sectional survey design in Kwara Central Senatorial District, using 611 respondents to whom structured questionnaires were administered. All the youths and women leaders from selected wards were engaged in an in-depth interview. The result indicated that 26.5% agreed that many people have fallen victim to cybercrime-ritualists in Kwara central senatorial district. The study concluded that addressing criminal victimization associated with cybercrime-ritualism required a comprehensive approach, with the recommendation that the Kwara state government should organise an anti-ritual program side by side with an anti-cybercrime program.